Cultural adaptation: the role of social media in the acculturation process among international students - Goh, Jia Tian; Ch'ng, Jocelyn Wen Pin; Tan, Hui Wen; Ong, Ching; Wong, Wei Fang (2019)
This study aims to address various issues faced by international students in UTAR Kampar by understanding their perception towards the factors that causes acculturative stress as well as the role of social media during the cultural adaptation process. The number of foreign students that come to Malaysia to further their study has increased eventually year by year. This study thereby assumes that Malaysia as a multicultural society, is easier for the foreign students to adapt themselves to the environment. Various research study has suggested different sources that cause the international students to suffer with acculturative stress. This research study aims to explore the perception of the international students in UTAR regarding the factors of acculturative stress if there will be any differences with other research study. Social networking sites are becoming more important in our daily life nowadays. People tend to use social media for different purpose. Therefore, this study would like to find out the importance of social media for UTAR’s international students and what are the role of social media for them? By knowing the international student’s perception regarding both of these matters, this study can suggest different ways for them to overcome the issues faced by them when they are in the host society. This can help the authority of university to take action toward the issues faced by the international students and thereby come out with better policy so that the students can easily adapt to the host society. This study matter will be discussed with the Integrative Communication Theory of Cross-Cultural Adaptation which discusses about the process of cross-cultural adaptation as and the factors that influence the level of cross-cultural adaptation. Besides, this study will also be discussed by using the dialectical model of intercultural adaptation which focus on the problem-solving strategies developed by the foreigners during their adaptation process. Throughout this research, we hope to bridge the gap which can contribute to the discussion from UTAR international students’ perspective. This research study will be done by conducting an in-depth interview within UTAR international students. This research study will use purposive sampling to target the participants who have specific criteria so that the data we collected will be more reliable. NVivo 11 will be used to analyze the data after the interview session. The conduct of this research will contribute to both theoretical and practical aspect which has made this topic more worth to be explored.